Patient safety events in hospital care of individuals with epilepsy. (28th June 2016) - Mendizabal, Adys; Thibault, Dylan P.; Willis, Allison W.
Summary: Objectives: (1) To describe patient adverse events (PAEs) experienced by hospitalized individuals with epilepsy and examine the association of an epilepsy diagnosis on risk of specific PAEs; (2) to examine the impact of a PAE on (a) length of stay (LOS), (b) inpatient death, and (c) use of institutional post‐acute care. Methods: We applied the Agency for Healthcare Research and Quality (AHRQ) Patient Safety Indicator (PSI) software to the National Inpatient Sample database to identify potential medical and postoperative PAEs among >72 million hospitalizations of adults in the United States from 2000 to 2010. Logistic regression models compared the odds of experiencing each PAE between hospitalizations of persons with epilepsy (PWE) and the general inpatient population. We also examined the impact of experiencing a PAE on LOS, inpatient death, and discharge disposition. Results: Hospitalized PWEs were at increased risk for specific postoperative PAEs: fall with hip fracture (Adjusted Odds Ratio, AOR 1.90, 1.21–2.99), respiratory failure (AOR 2.64, 2.43–2.87), sepsis (AOR 1.41, 1.21–1.63), and preventable postoperative death (AOR 1.25, 1.15–1.36). The odds of perioperative pulmonary embolism/deep vein thrombosis (AOR 1.65, 1.57–1.73), skin pressure ulcer (AOR 1.25, 1.22–1.29), and central venous catheter‐related bloodstream infections (AOR 1.24, 1.17–1.32) were also greater among hospitalizations of PWEs. Experiencing a PAE was associated with a prolonged mean length of stay (15 days vs. 5 days, t ‐test p < 0.001), a 416% increase in the odds of inpatient death (AOR 4.16, 3.95–4.38), and a 282% increase in use of high‐level post‐acute care (AOR 2.82, 2.72–2.93). Significance: Hospitalized adults with epilepsy are vulnerable to specific safety‐related adverse events, and these potential patient safety failures substantially impact outcomes and resource use. Efforts to reduce long‐term disability and improve the value of care delivered to PWEs may need to consider provider‐level interventions to reduce adverse events.